2020
DOI: 10.21203/rs.3.rs-45647/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduced efficacy of HIV-1 integrase inhibitors in patients with drug resistance mutations in reverse transcriptase

Abstract: Background: Little is known about the impact of pre-treatment drug resistance (PDR) to non-nucleoside reverse transcriptase inhibitors (NNRTIs) on the efficacy of second generation integrase inhibitors, now the standard of care drug class for HIV-1 treatment globally.Methods: We conducted next-generation sequencing on stored plasma specimens from the ADVANCE trial collected prior to treatment initiation. Our primary outcome was 96-week virologic success, defined as achievement of a viral load < 1000 copies/… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…An increased likelihood of VF among people with PDR on EFV/XTC/TDF was also observed in 2 recent large studies: a the phase 3, randomized clinical trial comparing TAF/FTC/DTG, TDF/FTC/DTG or TDF/FTC/EFV for first-line treatment of HIV-1 infection (ADVANCE) [ 44 ], in which VS among those with and without PDR was 65% and 85%, respectively ( P < .001), and a case-cohort substudy of the HIV/AIDS Drug Resistance Surveillance Study (ADReSS), enrolling 1000 patients initiating first-line efavirenz/emtricitabine/tenofovir in KwaZulu-Natal, South Africa [ 45 ], in which PDR was associated with a 3-fold greater risk of VF ( P = .002).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…An increased likelihood of VF among people with PDR on EFV/XTC/TDF was also observed in 2 recent large studies: a the phase 3, randomized clinical trial comparing TAF/FTC/DTG, TDF/FTC/DTG or TDF/FTC/EFV for first-line treatment of HIV-1 infection (ADVANCE) [ 44 ], in which VS among those with and without PDR was 65% and 85%, respectively ( P < .001), and a case-cohort substudy of the HIV/AIDS Drug Resistance Surveillance Study (ADReSS), enrolling 1000 patients initiating first-line efavirenz/emtricitabine/tenofovir in KwaZulu-Natal, South Africa [ 45 ], in which PDR was associated with a 3-fold greater risk of VF ( P = .002).…”
Section: Discussionmentioning
confidence: 74%
“…In addition, it has been suggested that the predictive value for virologic failure in people initiating EFV/XTC/TDF with NNRTI PDR with or without NRTI PDR may be different [ 44 ]. In a large South African study, the presence of NNRTI plus NRTI mutations vs no PDR was associated with longer time to VS (adjusted hazard ratio [aHR], 0.32 [95% CI, .12–.86]), whereas there was no difference in outcome between those with only NNRTI mutations vs no PDR (aHR, 1.05 [95% CI, .82–1.34]) at the 5% or 20% threshold [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most crucially, substitution of a single drug in a failing regimen must never be allowed since the development of resistance is a major concern, and drug resistance testing is not widely available in resource poor settings such as ours. 18 Our study has demonstrated excellent efficacy of DTG in both naïve and experienced patients, good tolerability and outcomes and therefore appears to be a better option for our patient population than an nonnucleoside reverse transcriptase inhibitors (NNRTI) based regimen. However, further studies will be required to determine superiority.…”
Section: Discussionmentioning
confidence: 75%
“…The implications for virological failure on TLD are not well understood [44], particularly if adherence is not an issue. In fact, recent data suggest that resistance to the NNRTI class of drugs also reduces the efficacy of TLD [45], but data have suggested dolutegravir with two NRTIs to be an effective second-line treatment [46]. The WHO has recently updated treatment guidelines to recommend immediate switching of regimens after a single elevated VL measurement [47].…”
Section: Discussionmentioning
confidence: 99%